Evaluation of natural water properties in the central and northern regions for ready biodegradability testing according to OECD 301A - Sompakdee, Nidtayaporn; Panpran, Jantana; Deecharern, Mirantee; Srasaengta, Nopphawan; Kahapana, Chanchai; Yueayai, Witthawat; Tungsatitporn, Sirorat; Pattanasupong, Anchana (Bulletin of Applied Sciences, 2024)
The evaluation of natural water properties for chemical compounds biodegradation test according to the OECD 301A including the verification of test method validity. The test method was using the natural water as the inoculum which collected from 3 provinces of central region, namely Nakhon Pathom, Samut Sakhon, and Ratchaburi, including 5 provinces of northern region, namely Kamphaeng Phet, Lampang, Phayao, Phichit and Nakhon Sawan. The quality of the collected natural water does not exceed surface water quality standards and still meets the OECD 301A standards requirement. In addition, the average biodegradation percentage of Sodium benzoate as the reference compound in the both of region were 86.13-97.53 throughout the study period, that achieve to the criteria according to OECD 301A, indicated that the biodegradation percentage of reference compound not less than 70% within 28 days test period. Therefore, it can be mentioned that the natural water from both areas are suitable for chemical compounds biodegradation testing according to the OECD 301A. Through this testing method, entrepreneurs in environmentally friendly products, both domestically and internationally, can benefit. It aids those aiming to enhance product properties related to biodegradation, ensuring compliance with international quality standards.